Impact of Heterogeneities on Sorption Capacities of Potential Paleozoic Gas Shales from Western Peninsular Malaysia - Syed, I.M. (Unconventional Resources Technology Conference (URTEC), 2021)
Natural gas, which is found as free, dissolved, and adsorbed gas, is abundant in organic-rich shales. Despite the growing relevance of sorbed gas, there are still questions about how lithological variables, as well as shale mineralogical, geochemical, and petrophysical features, influence gas sorption capacity. Therefore, the overall aim of this research was to relate variations in mineralogical, geochemical, and petrophysical properties of selected Paleozoic shale samples from Western Peninsular (WP) Malaysia comprising seven formations to their sorption capacities. Despite the apparent homogeneity at a mesoscale, micro-scale variations may exist between different ages and localities of the shales. These variations are significant enough to allow the classification of the shales into different categories based on their age instead of dealing with them as a single unit. Therefore, shales from WP Malaysia are grouped into four divisions i.e S-D (Silurian-Devonian), Devonian, Carboniferous, and Permian shales respectively. Low-pressure Nitrogen adsorption reveals older shales i.e., S-D and Devonian show higher average surface area and the lower average of pore diameter and total pore volume as compared to younger shales i.e., Carboniferous and Permian. The impact of methane sorption capacities (MSC) on studied shales revealed that total organic carbon (TOC) and Vitrinite Reflectance (Ro) are the primary controlling factor of methane adsorption on shale. However, S-D and Devonian shales revealed that TOC is not the primary factor as clay minerals contribute more towards MSC in these shales. Clay mineralogy roles are skeptical as they may have positive, negative, or sometimes no correlation with MSC. The impact of pore structure parameters i.e., pore diameter, pore-volume, and the specific surface area also shows the distinct influence on MSC. Furthermore, present investigations in shales help to understand the shale gas adsorption mechanisms and could deliver a scientific platform for the assessment and development of the green shale gas industry. Â© 2021 Unconventional Resources Technology Conference (URTeC)